An Analysis of Entailment in Lady Gaga’s Song Lyrics - Sitti Salma Malewa; Arman Arman (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This research aims to analyze Lady Gaga’s song lyrics in terms of pragmatic study. The problem concerns what are the types of entailment in those song lyrics. The objective of this research is to identify the types of entailment in seven song lyrics of Lady Gaga. This research used a qualitative descriptive method. Therefore, the data in this research are in the form of utterances conveyed by Lady Gaga. The source of the data is seven song lyrics of Lady Gaga. The data were collected by identifying, reading, coding, and classifying the data and then analyzed by presenting, describing, interpreting, and concluding the data. This research showed that among four types of entailment, the data involved all the types of entailment in Lady Gaga’s song lyrics. One-way entailment (5 times), Two-way entailment (4 times) Negative entailment (2 times), and Metaphorical entailment (9 times). Thus, those types of entailment are found in seven song lyrics of Lady Gaga.